Orthostatic symptoms does not always manifest during tilt-table test in pediatric postural orthostatic tachycardia syndrome patients - Tae-Eon Huh; Jung Sook Yeom; Young-Soo Kim; Hyang-Ok Woo; Ji Sook Park; Eun Sil Park; Ji-Hyun Seo; Jae-Young Lim; Chan-Hoo Park; Ki-Jong Park; Hee-Shang Youn (Korean Pediatric Society, 2013)
PurposeChronic day-to-day symptoms of orthostatic intolerance are the most notable features of postural orthostatic tachycardia syndrome (POTS). However, we have encountered patients with such symptoms and excessive tachycardia but with no symptoms during the tilt-table test (TTT). We aimed to investigate whether POTS patients with chronic orthostatic intolerance always present orthostatic symptoms during the TTT and analyze the factors underlying symptom manifestation during this test.MethodsWe retrospectively examined patients who presented with POTS at the Gyeongsang National University Hospital between 2008 and 2011. Diagnosis of POTS was based on chronic day-to-day orthostatic intolerance symptoms as well as excessive tachycardia during the TTT. The patients were divided two groups depending on the presentation of orthostatic symptoms during the TTT. Clinical data and the results of the TTT were compared between these groups.ResultsIn 22 patients, 7 patients (31.8%) did not present orthostatic symptoms during the test. Diastolic blood pressure (BP) was significantly lower in the symptom-positive group. The head-up tilt resulted in a significant increase in diastolic BP in the symptom-negative group (P=0.04), while systolic BP had a tendency to decrease in the symptom-positive group (P=0.06).ConclusionSignificant patients with POTS did not present orthostatic symptoms during the TTT despite having chronic daily symptoms. This finding may be important for establishing definitive diagnostic criteria for pediatric POTS. Development of symptoms during TTT might be related to low diastolic BP and abnormal compensatory responses to orthostasis.